Clinical testing of antiretroviral drugs as future prevention against vaginal and rectal transmission of HIV infection – a review of currently available results - Vysloužil Jakub; Kubová Kateřina; Tkadlečková Veronika Nováková; Vetchý David (Acta Pharmaceutica)
The original purpose of vaginally applied microbicides was to slow down the HIV epidemic among the population until an effective vaccination was developed. Nowadays, antiretrovirals applied in the form of gels or vaginal rings are considered most prominent in this field and are tested via vaginal or, rarely, rectal applications in numerous clinical studies (9 different antiretroviral drugs in 33 clinical studies, especially in Africa). Only tenofovir (1 % gel) and dapivirine (25 mg in vaginal ring) progressed into the phase III clinical testing. Their efficiency depended on the user´s strict adherence to the application regimen (for tenofovir 54 %, for dapivirine 61 % in participants over 25 years of age). Despite this, they are expected to be important and effective tools of preventive medicine in the near future. This review summarizes the results obtained during long-term clinical testing (2005–2018) of antiretroviral drugs against vaginal and rectal transmission of HIV infection.